PENGEMBANGAN SDM BERBASIS KOMUNITAS DI DESA WISATA PONCOKUSUMO: PELATIHAN SOFT SKILL KOMUNIKASI DAN PUBLIC SPEAKING MENUJU DESTINASI BERKELANJUTAN - Purwanto, Rhiza Eka; Saudah, Saudah; Lidiawati, Lidiawati; Mufita Y., Irma (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The community-based human resources development in Poncokusumo Tourism Village aimed to improve the capacity and skills of the community to support the sustainable progress of the village as a tourist destination. One of the important activities in this program is training in interpersonal communication, public speaking, and cross-cultural communication. It was held for the local community, especially MSME managers, homestay owners, and tour guides involved in the tourism management and development of the village. This training was carried out to strengthen communication skills between residents and with tourists, increase confidence in conveying information about the village's tourism potential, and build good relationships between the community and visitors. The material provided included basic techniques of effective communication, public speaking, and delivering interesting and clear messages, as well as tourism-related materials. The results showed that the participants experienced significant improvements in public speaking, interpersonal communication skills, and communication between cultures, with 90% of participants were able to answer tourists' questions confidently. This program also has a positive impact on Poncokusumo Tourism Village as a sustainable tourist destination, with more prepared and skilled people in managing interactions with visitors, which in turn increases the village's tourism appeal.